2020
DOI: 10.1002/ceas.12184
|View full text |Cite
|
Sign up to set email alerts
|

International Counseling Doctoral Students' Teaching Preparation: A Phenomenological Study

Abstract: We conducted a phenomenological study of teaching preparation with 11 international counseling doctoral students. We identified four primary themes: (a) international identity becomes salient in teaching, (b) acculturation occurs in teaching, (c) teaching is relational, and (d) support system is critical to teaching preparation. Multicultural implications for preparing international doctoral students as emerging counselor educators are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Accordingly, career development practitioners may help international students further hone their social skills that will enrich their integrated acculturation experience. Particularly, for international students whose first language is not English, career development practitioners may refer them to English speaking and writing programs as needed, which may not only enhance their English language skills but boost their self‐efficacy and self‐esteem as related to language (Li & Liu, 2020). Career development practitioners may also facilitate support groups for international students where they can receive information and exchange ideas about how to network with others both within and outside the classroom (Sullivan & Kashubeck‐West, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, career development practitioners may help international students further hone their social skills that will enrich their integrated acculturation experience. Particularly, for international students whose first language is not English, career development practitioners may refer them to English speaking and writing programs as needed, which may not only enhance their English language skills but boost their self‐efficacy and self‐esteem as related to language (Li & Liu, 2020). Career development practitioners may also facilitate support groups for international students where they can receive information and exchange ideas about how to network with others both within and outside the classroom (Sullivan & Kashubeck‐West, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The career development process is a central aspect of the international student experience (Balin et al., 2016). However, most of the research with international student populations has focused on acculturation concerns, social adjustment, language proficiency, and academic needs (e.g., Li & Ai, 2020; Li et al., 2017; Li & Liu, 2020; Li et al, 2018). Comparatively few studies have examined factors related to career decision‐making.…”
mentioning
confidence: 99%
“…The most common method of acquiring qualitative data through IPA is through thorough interviews (Smith, 2011 ), which were conducted through private and secure online video software while participants remained in the comfort of their natural settings throughout the recruitment and interview process. IPA studies were found throughout the health psychology and mental health literature (Smith, 2011 ), with similar models used to identify cultural needs within mental health training programs (Thomas & Brossoie, 2019 ), understand international counseling doctoral student preparation (Li & Liu, 2020 ), and explore social justice and multicultural competency in counseling school developmental models (Cook et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…With this model of English teacher, students are directed to essence and understanding rather than skill. On the other hand, some teachers have good English proficiency but do not understand linguistics (Li & Liu, 2020;Saafin, 2019). As a result, the teacher does not know what they are teaching because the material being taught relies heavily on books or dictionaries (Shanahan, 2020).…”
Section: Linguistics Proficiency In Eflmentioning
confidence: 99%